2013
DOI: 10.1039/c2tc00044j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene by low-temperature exfoliation and reduction of graphite oxide under ambient atmosphere

Abstract: We firstly report a facile approach to produce few-layered graphene sheets by low-temperature (130 C) exfoliation and reduction of graphite oxide under ambient atmosphere with the aid of HCl. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 23 publications
(29 reference statements)
6
74
0
1
Order By: Relevance
“…The effect of microwave treatment induced sparking, then burning in the graphite oxide powder to make an exfoliation and reduction of the material [15] .The final product washed by 1M HCl to remove a large pieces and not fully exfoliated GO powder and also some of HCl substance will remained into the inter-layers region of graphene during the washing process [18], and act as a spacers to prevent graphene sheets from restacking. It was found that the experiment take a lot of time as comparable to the different literature methods [14,19,20] may be due to using Hydrogen peroxide as oxidizing ageing in the preparation of (GO).…”
Section: Preparation Of Microwave Reduced Graphite Oxide (Mrgo)mentioning
confidence: 99%
“…The effect of microwave treatment induced sparking, then burning in the graphite oxide powder to make an exfoliation and reduction of the material [15] .The final product washed by 1M HCl to remove a large pieces and not fully exfoliated GO powder and also some of HCl substance will remained into the inter-layers region of graphene during the washing process [18], and act as a spacers to prevent graphene sheets from restacking. It was found that the experiment take a lot of time as comparable to the different literature methods [14,19,20] may be due to using Hydrogen peroxide as oxidizing ageing in the preparation of (GO).…”
Section: Preparation Of Microwave Reduced Graphite Oxide (Mrgo)mentioning
confidence: 99%
“…Thus significant efforts have been invested to develop methods for thermal exfoliation of GO at reduced temperatures. 152 Recently, few-layered graphene sheets by thermally exfoliating GO under high vacuum at a significantly low temperature of 200 °C were prepared, which is far below the proposed critical exfoliation temperature of 550 °C. 149 However, the surface area of the TRG sheets produced by this method is much lower (368 m 2 /g) than that of conventional thermally exfoliated graphene (around 600-900 m 2 /g).…”
Section: Thermal Methodsmentioning
confidence: 99%
“…The expanded force during the exfoliation of G-O originates from not only the release of gas like H 2 O and CO 2 by the decomposition of oxygen-containing functional groups in G-O, but also the negative pressure perpendicular to the surface of G-O produced by vacuum condition. We also substituted volatile substance for vacuum condition in the exfoliation of G-O [55]. The force resulting from the evaporation of volatile substance like HCl at 135-145 °C may surpass the van der Waals force within graphite interlayers, resulting in the full exfoliation of G-O under ambient atmosphere.…”
Section: Synthesis Of Graphenementioning
confidence: 99%